New species and records of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) from Jiangxi province, China - Shavrin, Alexey V. (Zootaxa, 2013)
The genus Lesteva Latreille, 1797 has been recently, intensively studied in China and twenty species are currently known from this vast territory (Rougemont, 2000; Watanabe, 2005; Li & al., 2005; Ma & al., 2012; Ma & Li, 2012). In this paper, I describe a new species of the genus with yellow round elytral spots, as well as provide records of L. (s.str.) pulcherrima Rougemont, 2000 and L. (s.str.) submaculata Rougemont, 2000 from Jiangxi province.